Public nuisance, public enemy, public servant?: introduction to the special issue on outlaw bikers in Europe - Lampe, Klaus von (Trends in organized crime)
This essay presents an introduction to the special issue on outlaw motorcycle clubs in Europe. Apart from providing an overview of the papers contained in the special issue, it presents a classificatory scheme for the analysis of the links between outlaw biker clubs-also known as outlaw motorcycle gangs (OMCGs)-and crime. Against the backdrop of the history of the outlaw biker subculture in Europe, this paper proposes a five-fold typology of criminal activities that can potentially by ascribed to biker clubs as organizational entities, and it presents three different scenarios for an overlap of criminal structures and the formal structure of an outlaw biker club.